Effects of Exercise Interventions on Inflammatory Parameters in Acutely Hospitalized Older Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The purpose of this systematic review and meta-analysis was to appraise the acute effects of exercise training on inflammatory parameters in hospitalized older adults. We conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Web of Science, Medline and PubMed were searched for studies published until August 2020. The review included all randomized controlled trials (RCTs) that evaluated and compared the effect of exercise versus usual care on inflammatory parameters in acutely hospitalized older adults. Two reviewers independently assessed the studies. The quality of all the included studies was assessed using the DerSimonian–Laird random-effects inverse-variance model. Five studies (275 participants) met the inclusion criteria. The exercise interventions included resistance or multicomponent intervention programs. The results indicate that, compared with usual care, exercise interventions have a positive impact on overall inflammatory parameters, including C-reactive protein (CRP) and insulin-like growth factor-I (IGF-1) (Hedge’s g = −0.19, 95% confidence interval [CI] −0.33 to −0.04, p = 0.011, I2 = 0%). However, analyses of individual inflammatory parameters revealed a non-significant trend for reductions in CRP (Hedge’s g = −0.20, 95% CI −0.47 to 0.07, p = 0.151, I2 = 31.2%) and IGF-I (Hedge’s g = −0.34, 95% CI −0.79 to 0.11, p = 0.138, I2 = 0%). On the basis of this review, we conclude that exercise during acute hospitalization offers a mild improvement in the inflammatory profile over usual care in older patients. Nevertheless, due to limited number of RCTs, our findings must be interpreted with caution and confirmed in future studies. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.